UNBOUNDED CHRISTOLOGIES: THE CASE OF WIDOWS’ CHRISTOLOGY – ‘JESUS CHRIST IS BREATH’ - Maseno-Ouma, Loreen (Scriptura, 2015)
This article draws upon African widowhood for theological reflection. It shows that experiences of widowhood characterize widows in rural western Kenya as liminal individuals located at a threshold. These widows experience deep loneliness besides other hardships. Further, they feel an existential lack of appeasement of loneliness, which opens up room for the emergence of variant Christologies that are fluid and concern intermediate (‘in between’) areas of experience. Thus this new dynamic of specific embodied experiences by African widows and the intermediacy they experience create the possibility for widows to see Jesus Christ in a manner which is similarly fluid, shifting, ‘in between’ and on the threshold. In order to capture this new Christology that is unbounded and creative, through metaphoric theology, "Jesus Christ is breath" articulates who widows in rural western Kenya say Jesus Christ is.